Pearl: joias makers - Moraes, Virgínia Rúbia Alves Ferreira Xavier de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Not available

Não disponível
Keywords: Jóias; Projeto de produto; Desenho industrial